2016
DOI: 10.1039/c6cp01706a
|View full text |Cite
|
Sign up to set email alerts
|

Computational insights into intriguing vibration-induced pulsing diradical character in perfluoropentacene and the perfluorination effect

Abstract: As an n-type organic semiconductor compound, perfluoropentacene has more widespread applications in organic electronics because of its higher electron mobility compared with its parent pentacene. Herein, we explore intriguing dynamic electronic properties of perfluoropentacene caused by structural vibrations using density functional theory calculations. Perfluoropentacene could exhibit diradical character because of the persistent vibrations, although it belongs to a closed-shell singlet molecule in its equili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Undoubtedly, these findings have fully confirmed that molecular vibration could lead to the expected or unexpected effects in charge transfer or other electronic dynamics applications. Furthermore, our group also theoretically demonstrated that molecular inherent vibrations could induce intriguing dynamic diradical character in pentacene, hexazapentacene, and perfluoropentacene . Besides, the β‐turn motifs have been found to be more flexible than the β‐sheet motifs in controlling the efficiency of proton transfer between reactive centers and should also play an intriguing role in assisting charge transfers.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Undoubtedly, these findings have fully confirmed that molecular vibration could lead to the expected or unexpected effects in charge transfer or other electronic dynamics applications. Furthermore, our group also theoretically demonstrated that molecular inherent vibrations could induce intriguing dynamic diradical character in pentacene, hexazapentacene, and perfluoropentacene . Besides, the β‐turn motifs have been found to be more flexible than the β‐sheet motifs in controlling the efficiency of proton transfer between reactive centers and should also play an intriguing role in assisting charge transfers.…”
Section: Introductionmentioning
confidence: 91%
“…To examine the gradual variations of the relaying properties in vibrational progress of a specific vibrational mode, the dynamic process of a specific vibrational mode is represented by a given number of consecutive snapshots, and hence described by R = R 0 ± n Δ R , where Δ R is an increment of coordinate change and n = 1–10, while + n Δ R and – n Δ R denote the positive and negative shifts, respectively. This method has been proved to be suitable to discussing the vibrational effects in our previous work . Further, the corresponding energies of neutral and anionic distorted and static configurations, spin density distributions, and LUMO and SOMO energies were obtained.…”
Section: Calculational Detailsmentioning
confidence: 99%
“…Furthermore, our results show that the optimized configuration of ZP in S 1 state is a non-planar structure induced by the nitro rotation accompanied with electron localization on nitro group, which indicates the lowest excited singlet state of ZP possesses charge-transfer character. It is wellknown that the molecular distortion induced by the vibration is an inherent property of a molecule, which can also be activated by external energy pulse and lead to the changes of the geometric as well as the electronic properties (Huynh and Meyer, 2007;Sánchez-Carrera et al, 2010;Zimmerman et al, 2013;Feng et al, 2016;Zhang et al, 2016). Accordingly, it is worth illustrating the influence of nitro rotation on the absorption spectra and electron distribution of the system.…”
Section: Introductionmentioning
confidence: 99%